1992
DOI: 10.2307/3283330
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Genetic Factor Influencing Protection from Infection with Ascaris lumbricoides in Nigerian Children

Abstract: An epidemiological study of Ascaris lumbricoides infections was carried out in primary school children aged 5-16 yr from Ile-Ife, Nigeria. Intensity of infection was assessed directly by means of counting worms passed during a 48-hr period after chemotherapy. Reinfection patterns of A. lumbricoides were assessed at 2 6-mo intervals and statistical evidence of predisposition to infection status was obtained. An investigation of 3 groups of children who were judged to be predisposed not to be infected, to be lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 2 publications
0
14
0
1
Order By: Relevance
“…The possibility that this commonly observed overdispersion is due to host genetic factors has been explored in a number of studies. For example, a study of Nigerian children aged 5-16 years found evidence for a role of the major histocompatibility complex in determining patterns of Ascaris infection [5].Most previous genetic studies of soil-transmitted helminthic infections [6 -12] have focused on relatively small sample sizes and simple pedigree structures, as shown in table 1. The majority of these studies were quantitative genetic assessments of the heritabilities of helminth infections as assessed by eggs per gram of feces, with between 0% and 39% of the variation being attributable to genetic factors.…”
mentioning
confidence: 98%
“…The possibility that this commonly observed overdispersion is due to host genetic factors has been explored in a number of studies. For example, a study of Nigerian children aged 5-16 years found evidence for a role of the major histocompatibility complex in determining patterns of Ascaris infection [5].Most previous genetic studies of soil-transmitted helminthic infections [6 -12] have focused on relatively small sample sizes and simple pedigree structures, as shown in table 1. The majority of these studies were quantitative genetic assessments of the heritabilities of helminth infections as assessed by eggs per gram of feces, with between 0% and 39% of the variation being attributable to genetic factors.…”
mentioning
confidence: 98%
“…An analysis of A. lumbricoides worm loads in Nigerian children suggested the involvement of the major histocompatibility complex (MHC) in determining resistance to infection. 28 Similarly, the MHC has been associated with severity of outcome in schistosomiasis. 29 Although compelling, such association studies of candidate genes have potentially major statistical problems that can lead to false-positive results.…”
mentioning
confidence: 99%
“…While the generative mechanisms of predisposition are currently unknown, it is believed that host genetics may play a major role [56][57][58][59][60][61]. Familial patterning to Ascaris infection has been M A N U S C R I P T indicates that the genetic factors influencing the host's capacity to respond protectively to infection are polygenic, specified by many minor susceptibility genes rather than primarily by a few major loci [62].…”
Section: Dissecting Genetic Control Of Resistance To Helminth Infectionmentioning
confidence: 99%